Russian and Bulgarian Phraseological Neologisms as Objects of Dictionary Description - S. G. Shulezhkova (Научный диалог)
The issues related to the transformation of Slavic languages at the turn of the 20th - 21st centuries are considered. Special attention is paid to the tendencies of enrichment of Bulgarian and Russian languages with phraseological units. The novelty of the study is seen in the fact that for the first time a comparative analysis of dictionaries containing phraseological neologisms is made. The results of a comparison of the sources of phraseological units and their areas of functioning are presented. The author proceeds from the fact that the enrichment of phraseology is subject to two trends - borrowing and updating at the expense of its own reserves. It is established that borrowed phraseological units are represented by calques, semi-calques and units that preserve the original sound appearance. It is emphasized that they function in technical, political, financial, military, sport and other spheres of communication. The author dwells on the differences between Bulgarian and Russian neologisms: Bulgarians have mainly folk and folklore units; Russians have many expressions from synthetic genres of art. The higher productivity of such “suppliers” of neologisms as international political discourse, military and slang spheres in the Russian language, and financial and economic sphere in the Bulgarian language is proved. The relevance of the study is proved by the need to create the Russian-Bulgarian and Bulgarian-Russian dictionaries of phraseological neologisms.